Authoritative glossary, universal trait order, and standardized checklists of taxonomically informative traits for the extant Cycadales - Haynes, Jody L. (Phytotaxa, 2026)
Changing rules of botanical nomenclature, varying quality of species descriptions, and inconsistent use and assessment of morphological traits and the terms used to describe them have long contributed to confusion in cycad taxonomy. The rules of botanical nomenclature have since stabilized and protologue format has become more consistent, but inconsistent trait selection, assessment, and terminology persist in contemporary taxonomic works. This paper expands upon the guidelines for future taxonomic works of Osborne & Walters (2004a) and the supplemental protocols for improving trait assessment consistency of Haynes (2026) by providing an authoritative glossary of trait and character state terminology, standardized genus-specific checklists of taxonomically informative traits, and a universal trait order for formal taxonomic treatments within the Cycadales.